2021
DOI: 10.1101/2021.04.11.439336
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete neuroanatomy of dragonfly wings suggests direct sensing of aeroelastic deformations

Abstract: Fly-by-feel describes how flying animals capture aerodynamic information via their wings' sensory system to implement or enhance flight control. Traditional studies on animal flight emphasized controlling body stability via visual or inertial sensory inputs. In line with this, it has been demonstrated that wing sensory systems can provide inertial state estimation for the body. What about the state estimation of the wings themselves? Little is known about how flying animals utilize their wing sensory systems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 111 publications
(155 reference statements)
0
4
0
Order By: Relevance
“…For example, the dragonfly, a highly maneuverable aerial predator, may require relatively fast hemolymph flows to supply the extensive network of sensory structures throughout its wings. 6,10 In comparison, a migratory insect such as a monarch butterfly, which often glides along air currents and needs to maximize energetic efficiency to travel long distances without feeding, may instead benefit from slower wing hemolymph flows, which require less active pumping..In addition, flow speeds are likely to vary widely within insect orders such as Lepidoptera, which display enormous variation in body size.…”
Section: /14mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the dragonfly, a highly maneuverable aerial predator, may require relatively fast hemolymph flows to supply the extensive network of sensory structures throughout its wings. 6,10 In comparison, a migratory insect such as a monarch butterfly, which often glides along air currents and needs to maximize energetic efficiency to travel long distances without feeding, may instead benefit from slower wing hemolymph flows, which require less active pumping..In addition, flow speeds are likely to vary widely within insect orders such as Lepidoptera, which display enormous variation in body size.…”
Section: /14mentioning
confidence: 99%
“…12 Recent work has also confirmed that hemolymph circulation is necessary for the scent-producing organs on lepidopteran wings 4 and the hundreds of sensory hairs distributed across dragonfly wings to function properly. 6,10 Despite this wide range of important physiological functions, insect wings have primarily been studied in relation to their mechanical function during flight. Structurally, insect wings are composed of chitinous, tubular veins and thin, membranous regions 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While scale cell color diversity is the most prominent feature of butterfly wings, wings also display a variety of other cell types that differentiate at multiple locations. Innervated sensory cells, often placed on top of veins (Dickerson et al, 2014;Yoshida and Emoto, 2011;Yoshida et al, 2001), are involved in mechanosensory or chemosensory functions (Aiello et al, 2021;Fabian et al, 2022;Hartenstein and Posakony, 1989) and glandular secretory cells are responsible for producing and secreting sex pheromones, mostly in males (Dion et al, 2016). How such wing cell type diversity is genetically and developmentally regulated remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%